2023
DOI: 10.3390/biomedicines11010218
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell Therapy Reverses Detrusor Hypoactivity in a Chronic Kidney Patient

Abstract: Detrusor hypoactivity (DH) is characterized by low detrusor pressure or a short contraction associated with low urinary flow. This condition can progress to chronic renal failure (CRF) and result in the need for dialysis. The present case report demonstrates that a patient diagnosed with DH and CRF who received two transplants with 2 × 106 autologous mesenchymal stromal cells at an interval of 30 days recovered the contractile strength of the bladder and normalized his renal function. The patient had a score o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These sources include adult and fetal tissues and human embryonic stem cells (hESCs). Although clinical trials with stem cell therapy have been reported in erectile dysfunction, 10 stress urinary incontinence, 11 and detrusor underactivity, 12 none have been conducted for IC/BPS in the field of urology.…”
Section: Why Is Stem Cell Therapy a Potential Candidate For Interstit...mentioning
confidence: 99%
“…These sources include adult and fetal tissues and human embryonic stem cells (hESCs). Although clinical trials with stem cell therapy have been reported in erectile dysfunction, 10 stress urinary incontinence, 11 and detrusor underactivity, 12 none have been conducted for IC/BPS in the field of urology.…”
Section: Why Is Stem Cell Therapy a Potential Candidate For Interstit...mentioning
confidence: 99%
“…This indicates a slight or significant improvement in UAB symptoms. Recently, Coelho et al reported on a 54-year-old male patient who underwent intravesical injections of autologous mesenchymal stromal cells (AMSCs) [156]. The patient demonstrated a significant reduction in PVR from 800 mL to 20 mL as well as marked improvements in the maximum flow rate from 2 mL/s to 23 mL/s, maximum detrusion pressure from 21 cmH 2 O to 46 cmH 2 O, and BCI from 31 to 161.…”
Section: Stem Cell Therapymentioning
confidence: 99%